PENERAPAN MODEL PEMBELAJARAN ROLE PLAYING UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS III SDN 15 AIR JAMBAN - Darmayanti Darmayanti; Syahrilfuddin Syahrilfuddin; Hamizi Hamizi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This research was backgrounded by the problem of low learning outcomes of social sciences of the third grade students SDN 15 Air Jamban, with an average value of 60.4. For that conducted a classroom action research as many as 2 cycles to students of class III SDN 15 Air Jamban totaling 26 students, consisted of 15 male students and 11 female students started from February to May 2015 which aimed to improve result social sciences students by implementing role playing model. From the results of data analysis improving student learning outcomes, preliminary data showed that the average value of the class only 60.4 it meant students who completed only 9 (34.6%), meanwhile the students who did not completed total 17 persons (65.4%). After doing the action in the first cycle by implementing role playing model, the value of average daily test on the first cycle to 70.8 it meant increased of 17.22%. Students who pass increased to 15 with the classical completeness reached 57.7%. In the daily test cycle II obtained the average value of the class of 85.7 by the number of students who completed 23 people and who did not completed just 3 people. It meant that the learning outcomes increased by 26.47% with the classical completeness reached 88.5%. Thus, it can be concluded that the implementation of cooperative learning model can improve social sciences learning outcomes of the third grade students SDN 15 Air Jamban.Keywords: Role Playing, Learning Outcomes of IPS